Managing Communication Between Intelligence and Security Unit Personnel and Informants in the Prevention of Public Order Disturbances: Developing a Trust-Based Communication Model - Toni Dwi Pamuji; Agus Ganjar Runtiko; Nana Sutikna (International Journal of Social Science and Religion (IJSSR), 2026)
This study examines interpersonal communication patterns between police intelligence personnel (Intelkam) and informants in preventing public safety disturbances. The focus is on trust-based communication, i.e. how building trust serves as the foundation for effective information gathering. A qualitative design was used, with data from in-depth interviews and field observations (user’s thesis document) analyzed thematically. Key findings highlight that face-to-face and informal (familial) communication foster openness, empathy, and supportiveness (per DeVito’s model), encouraging informants to share information. Trust-building strategies include personal approach (understanding informant’s character), safeguarding informant confidentiality, and maintaining ongoing contact. Main communication barriers are initial distrust and safety concerns of informants. A conceptual model is proposed linking communication patterns (face-to-face, phone, informal) through interpersonal qualities (openness, empathy, support) to trust, which in turn enhances information quality and prevention effectiveness. Theoretically, this extends interpersonal communication theory to intelligence context; practically, it suggests training officers in transparent, supportive communication. Study limitations involve case study scope and secondary data, so future research should empirically test the model in broader settings.